Case study on performance monitoring and stability analysis of Baishihu suspension bridge and side slope - Chen, Chihcheng; Shih, Ban-Jwu; Jeng, Ching-Jiang (Journal of Civil Engineering and Management, 2022)
The main structure of the Baishihu suspension bridge was connected to the anchor foundations by three main steel cables. The wooden pedestrian deck was fixed to the main steel cables using steel beams and was stabilized by two stabilizing cables. The stabilizing cables and bridge body were joined by 44 steel connecting rods. Therefore, the slope stability at the anchorage foundations of the main steel cables, as well as the performance monitoring and analysis of the main steel cables and stabilizing cables, are critical to the overall performance of the suspension bridge. This paper discusses the performance monitoring and analysis of the steel cable deflection and cable strength for this bridge, as well as the main considerations and results of the stability analysis of the bridge abutments and side slopes of the two banks. Water-level observation wells, inclinometers, and tiltmeters monitoring were used to record reference data for the analysis of the slope stability performance. Additionally, the three-dimensional dynamic analysis program VFIFE was used to analyze the deformation and motion of the bridge. The final steady-state results were used to compare the static design value and monitoring data. The dynamic response before the final steady state was also observed.